Presentation - Editores (Farol, 2024)
Issue 28 of the already consolidated Farol Magazine has as its main axis concepts that shape the thematic dossier “Feminism and decoloniality”. The articles included here attest to the significant influence that these theoretical and political currents have had on contemporary art. This means, as it is reasonable to think today, the reordering, or cultural aggiornamento – along with the profound transformation of the dialectic of the art/criticism relationship that allows, in the form of a mobile constellation of statements, the researcher to theorize the meaning and positioning of practices in relation to a set of disciplines – aesthetics, philosophy, history, anthropology, psychoanalysis, technology, invention and, essentially, art – as well as a discursive and visual context that involves it culturally and socially.